2005
DOI: 10.1080/09286580591000836
|View full text |Cite
|
Sign up to set email alerts
|

Uveal and Conjunctival Malignant Melanoma in Denmark, 1943–97: Incidence and Validation Study

Abstract: The incidence of malignant melanoma in the ocular region was stable in contrast to a major increase in cutaneous melanoma in Denmark during the period 1943-97. The incidence of iris melanomas increased substantially, whereas the rate was stable for choroid/ciliary body and conjunctival melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
2
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 55 publications
3
61
2
7
Order By: Relevance
“…26,27 Contrary to previous reports, which have shown a slight predominance of males, 28 we found no statistically significant differences in the crude or age-adjusted incidence rates between genders. Although not fully comparable, the annual incidence of ocular melanoma in Norway has been reported to be 7.0 for women and 9.0 for men, 29 which indicates that the incidence of uveal melanoma has been relatively stable over the past several decades.…”
Section: Discussioncontrasting
confidence: 99%
“…26,27 Contrary to previous reports, which have shown a slight predominance of males, 28 we found no statistically significant differences in the crude or age-adjusted incidence rates between genders. Although not fully comparable, the annual incidence of ocular melanoma in Norway has been reported to be 7.0 for women and 9.0 for men, 29 which indicates that the incidence of uveal melanoma has been relatively stable over the past several decades.…”
Section: Discussioncontrasting
confidence: 99%
“…1,3,21 Although some studies describe an equal incidence in men and women, 2,3 others have reported higher frequency in male patients. 2,21 Clinical picture…”
Section: Epidemiologymentioning
confidence: 99%
“…The incidence rate of choroidal and ciliary body melanomas has been estimated to 0.6 per 100 000 person-years [1]. These tumours are primarily handled by enucleation or radiotherapy with some treated by local resection or other modalities.…”
mentioning
confidence: 99%